Business : - Jennings, Marianne (Thomson/West, 2006)
The text provides superior legal, ethical, and regulatory coverage while fully integrating practical business practices for tomorrow's business managers. Legal topics are explored and explained through real-world business examples (over 300 references to business are made in the text). In addition to a solid foundation in the law, students learn valuable legal and ethical reasoning skills through a variety of critical thinking exercises. Students receive -- and appreciate -- practical advice on when it is necessary to call a lawyer, how best to use legal aid services and how to avoid legal trouble in the first place